Ответы и объяснения

  • IOriOnI
  • почетный грамотей
2012-05-22T18:33:08+04:00

№1

Log3 (x+1) + log√3 (x+1) +log1/3 (x+1)=6

ОДЗ: x+1>0  ->x> -1

Log3 (x+1) + log√3 (x+1) +log1/3 (x+1)=6

log√3 (x+1) = 1/2log3 (x+1)

log1/3 (x+1) = - log3 (x+1)

Log3 (x+1) +1/2log3 (x+1) - log3 (x+1)=6

Log3 (x+1) = y

Y+1/2y-y=6

1/2y=6

Y=12

Log3 (x+1) = 12

312 = x+1

X=312 – 1

 

№3

Log(x+1) (x2 -2x+1) = 1

ОДЗ: х+1 >0;  x+1 не равен 1(=>x не равен 0); x2 -2x+1>0

(x+1)1  = (x2 -2x+1)

X+1 = x2 -2x+1

x2 -3x=0

x(x-3)=0

x=0 – не подходит

x=3

 

Это все во вложении!